Open letter to the leader of academic medicine. Issue 7586 (25th January 2007) - Ioannidis, John P A; Ahmed, Tahmeed; Awasthi, Shally; Clarfield, A Mark; Clark, Jocalyn; Dandona, Lalit; Howe, Amanda; Lozano, Juan M; Li, Youping; Madani, Hardi; Marusic, Ana; Mohammed, Idris; et al.
Abstract : As their campaign comes to a close, ICRAM presents a challenge to academic medicine's invisible leaders